CORRELATION BETWEEN SERUM LEVEL GALECTIN-3 AND EARLY REMODELLING INDICATOR OF LEFT VENTRICLE IN PATIENT WITH ACUTE MYOCARDIAL INFARCTION DURING PRE-PERCUTANEOUS CORONARY INTERVENTION - I Nyoman Indrawan Mataram; Wayan Aryadana; AA Wiradewi Lestari (Jurnal Kardiologi Indonesia, 2019)
Background: Coronary heart disease (CHD) is a leading cause of death worldwide. Acute coronary syndrome (ACS) is a spectrum of CHD. Left ventricle remodelling is one of the complication with the bad outcome either short-term or long term. Early remodelling process (within 0-72 hours) post infarction can be assessed by circulating biomarker (Galectin-3), echocardiography, coronary angiography, and clinically. Objective: The aim of study is to know the correlation between serum level of Galectin-3 and early remodelling indicator in patient with acute myocardial infarction during pre-percutaneous coronary intervention. The parameters are LVEDV, LVEF, diastolic function component, TIMI flow, MBG, and presence of acute heart failure. Materials and Methods: This cross sectional study was conducted in Sanglah General Hospital during March-May 2018. A 62 sample was determined consecutively. Results: Bivariate analysis with Spearman correlation shows Galectin-3 correlated with LVEDV (r = 0,808; p= 0,000), E/e’ average (r = 0,297; p = 0,019), E/A ratio (r = 0,261; p= 0,041), and MBG (QuBE) (r = 0,647; p = 0,000). No correlation was found between Galectin-3 and LVEF Teich (r = -0,213; p= 0,097), LVEF Biplane (r = -0,226; p = 0,077), LAVI (r = 0,301; p = 0,170), e’septal (r = -0,079; p = 0,539), e’lateral (r = -0,092; p = 0,476), and TR Vmax (r=0,068; p=0,600). Chi square analysis shows no association between Galectin-3 and diastolic dysfunction left ventricle (OR= 1,032, p= 0,966, CI95%= 0,239-4,462), TIMI flow (OR= 1,032, p= 0,966, CI95%= 0,239-4,462), MBG score (OR= 0,264, p= 0,197, CI95%= 0,031-2,259), and acute heart failure (OR=0,577, p= 0,476, CI95%= 0,127-2,617). Multivariat analysis with multiple linear regression shows an increase in Galectin-3 has been proven associated independently with LVEDV, LAVI, E/e’ average, and E/A ratio. Multiple logistic regression shows Galectin-3 has not been proven independently with diastolic dysfunction, TIMI flow, MBG score, and acute heart failure. LVEDV is the best outcome that can be explained as its value influenced by constant, BMI, and Galectin-3 (R2 = 0,509). Conclusion: Galectin-3 correlated with LVEDV, average E/e’, E/A ratio, and MBG (QuBE). There is an independent association between Galectin-3 and LVEDV, LAVI, average E/e, and E/A ratio. Early remodelling process within 0-72 hours post infarction was happened pre-PCI. Anti-remodelling (including anti failure) during early phase is strongly recommended in order to prevent worse outcome in short and long term. Keywords: Galectin-3, early remodelling left ventricle, acute myocardial infarction, percutaneous coronary intervention.